Analysis of the technical feasibility of ecological bricks based on PET plastic and bottle glass for the reduction of solid waste pollution in a metropolis - Arguedas, Jessica (2024)
Contamination by non-biodegradable solid waste is worrying, mainly due to PET and glass waste, because they are used for single use such as bottles or containers. In addition, global production in 2021 of these materials was 139 million tons and 23.4 million tons, respectively. Therefore, the objective of this research is to develop an efficient design of bricks composed of cement, PET plastic and glass, evaluating both their physical properties and their mechanical properties to reduce said waste. For this, 4 mixtures based on cement, sand and glass were designed with proportions of 1:2:0.5 and 1:2:1. In addition, 5% and 10% PET were incorporated into these proportions. It should be noted that the PET was ground to a size of 0.2 cm and the glass was ground to a size of 2 cm. The tests carried out show that the 1:2:0.5 dosage with 10% PET is the most efficient, since it obtained a compressive strength of 77.99 kg/cm2 after 28 days. Therefore, it exceeds the minimum value of 70 kg/cm2 after 28 days to be classified as type II brick according to the masonry standard E.070. Likewise, said unit complied with the warping, dimensional variation and absorption tests required by the aforementioned standard.